Pengaruh Persepsi Kepercayaan dan Persepsi Nilai terhadap Behavior Intention melalui Satisfaction sebagai Variabel Intervening pada Mobile Banking - Widia Apriani; Unik Dwi Lestari (Tamilis Synex: Multidimensional Collaboration, 2024)
The new technological wave that hit the financial industry has changed many traditional banking structures. Factors such as online banking, self-service machines, financial integration and 24-hour access have changed views on the need for digital banking. The main objective of this study is to analyze the effect of perceived trust and perceived value on behavior intention with satisfaction as an intervening variable for digital wallet users in Indonesia. The sampling technique used in this study was purposive sampling with the nonprobability sampling method. The number of respondents used in this study amounted to 145 respondents with the criteria of digital wallet users in Indonesia and who had made transactions at least 2 times. The analytical method used is Partial Least Square Structural Equation Modeling (PLS-SEM). The results of this study prove that perceived trust and perceived value by users can increase satisfaction. The higher the value of customer satisfaction, the higher the behavioral intention for digital wallets in Indonesia. Perception of trust has a positive effect on behavior intention. In addition, perceived value and perceived trust indirectly have a positive effect on behavior intention through satisfaction. This can provide input to the management of digital wallet companies in increasing behavior intention by increasing perceptions of trust and perceived value.